The Influence of Workload and Physical Work Environment on the Performance of Lecturers and Employees at Prasetiya Mandiri Polytechnic PSDKU Palembang - Rovita, Desi; Hildayanti, Siti Komariah; Roswaty (Jurnal Ilmiah Ekonomi Global Masa Kini, 2025)
Workload and physical work environment have an impact on performance. This study was conducted to determine and analyse the impact of workload and physical work environment on the performance of lecturers and employees at Prasetiya Mandiri Polytechnic PSDKU Palembang. The sampling technique used was a saturated sample of 52 respondents. The data obtained in this study were collected through questionnaires, observations, interviews, and literature studies. The data analysis technique in this study used SPSS software version 22, which consisted of data quality tests, classical assumption tests, multiple regression analysis, and hypothesis testing. The results of the study show that, partially, workload has a negative and significant effect on performance, while the physical work environment has a positive and significant effect on performance. Simultaneously, it was found that workload and the physical work environment have a positive and significant effect on the performance of lecturers and employees at Prasetiya Mandiri PSDKU Palembang Polytechnic. The correlation coefficient (R) test obtained a value of 0.486, which means that the level of relationship between the variables of workload (X(1) )and work environment (X(2) )on the performance variable (Y) has a moderate level of relationship. The coefficient of determination (R²)obtained a value of 0.236, indicating that the contribution of the workload and physical work environment variables can explain 23% of the performance variable, while the remaining 77% is explained or influenced by other variables not examined in this study. Keywords: Workload, Physical work environment, Performance, Influence, Significant